Social Performance of Islamic Microfinance Institutions: Examining the Financial Sustainability as Driving Factor - Hesi Eka Puteri; M. Arifin; Hidayatul Arief (Jurnal Internasional Penelitian Bisnis Terapan, 2022)
This study examines the impact of financial sustainability on the achievement of IMFIs (Islamic Microfinance Institutions)’ social performance. It is a quantitative study supported by a survey on six units of Islamic Rural Banks in the province of West Sumatera, Indonesia, from 2012 to 2018. This study used secondary data collected from the publication of financial services authority and other financial documents of Islamic Rural Banks. The data were analyzed by implementing the Panel Data Regression. The results indicate that financial sustainability, proxied by Return on Assets (ROA) and Return on Equity (ROE), affects social performance achievement. These findings elaborate on the previous studies that identify a relationship between these two aspects in microfinance institutions. The existence of a new predictor in the model, NOM (Net Operating Margin), has proven to give unsignificant impact on the achievement of IMFIs’ social performance. This study concludes that financial sustainability is the driving factor in determining the achievement of IMFIs’ social functions. Thus, strengthening financial sustainability will greatly impact the achievement of IMFIs’ social function in their role as community banking.